Chromosome mapping of a Tc1-like transposon in species of the catfish Ancistrus - Silva, Keteryne Rodrigues da [UNESP]; Mariotto, Sandra; Centofante, Liano; Parise-Maltempi, Patricia Pasquali [UNESP] (Pensoft Publ, 2017)
The Tc1 mariner element is widely distributed among organisms and have been already described in different species of fish. The genus Ancistrus (Kner, 1854) has 68 nominal species and is part of an interesting taxonomic and cytogenetic group, as well as presenting a variation of chromosome number, ranging from 2n=34 to 54 chromosomes, and the existence of simple and multiple sex chromosome system and the occurrence of chromosomal polymorphisms involving chromosomes that carry the nucleolus organizer region. In this study, a repetitive element by restriction enzyme, from Ancistrus sp. 1 Flecha was isolated, which showed similarity with a transposable element Tc1-mariner. Its chromosomal location is distributed in heterochromatic regions and along the chromosomal arms of all specimens covered in this study, confirming the pattern dispersed of this element found in other studies carried out with other species. Thus, this result reinforces the hypothesis that the sequence AnDraI is really a dispersed element isolated. As this isolated sequence showed the same pattern in all species which have different sex chromosomes systems, including in all sex chromosomes, we could know that it is not involved in sex chromosome differentiation.
Keywords: Repetitive DNA; enzyme digestion; chromosomal mapping; transposable elements; in situ fluorescence hybridization